PENGARUH EKSTRAK LIMBAH UDANG, EKSTRAK DAUN LAMTORO, DAN LARUTAN ECO-ENZYME DENGAN NUTRISI AB MIX TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAYURAN SAWI (Brassica juncea L). SECARA HIDROPONIK NFT. - M. Ridho Arisman; Darwin Pangaribuan; R.A Diana Widyastuti; Soesiladi Esti Widodo (BPFP Universitas Bengkulu, 2026)
[GROWTH AND YIELD RESPONSE OF MUSTARD GREENS (Brassica juncea L.) TO COMBINED APPLICATION OF CHICKEN MANURE EXTRACT, RABBIT URINE EXTRACT, AND AB-MIX NUTRIENT SOLUTION IN AN NFT HYDROPONIC SYSTEM]. Hydroponic cultivation offers several advantages over conventional agricultural practices, including the production of clean produce, accelerated plant growth, improved crop quality, and increased yield. Moreover, hydroponic systems provide a cost-effective approach for vegetable production with distinct agronomic benefits. This study aimed to evaluate alternative nutrient formulations to partially replace AB-Mix fertilizer using chicken manure extract and rabbit urine extract. The experiment was conducted in a field garden located in Labuhan Ratu District, Bandar Lampung City, from June to July 2024. A Completely Randomized Design (CRD) was employed, consisting of four treatments with six replications, involving a total of 144 mustard green plants. The treatments included: (1) 75% AB Mix + 25% chicken manure extract; (2) 75% AB Mix + 15% chicken manure extract + 10% rabbit urine extract; (3) 50% AB Mix + 30% chicken manure extract + 20% rabbit urine extract; and (4) control (100% AB Mix). Data were subjected to a homogeneity test using Bartlett’s test. Upon meeting the assumptions, analysis of variance (ANOVA) was performed, followed by mean separation using the Least Significant Difference (LSD) test at a 5% significance level. The results indicated that the application of 75% AB Mix combined with 25% chicken manure extract, as well as 75% AB Mix combined with 15% chicken manure extract and 10% rabbit urine extract, showed no significant difference compared to the control (100% AB Mix). In contrast, the treatment consisting of 50% AB Mix combined with 30% chicken manure extract and 20% rabbit urine extract differed significantly from the control. These findings suggest that partial substitution of inorganic AB Mix fertilizer with organic nutrient sources, such as chicken manure extract and rabbit urine extract, has the potential to reduce dependence on inorganic fertilizers in hydroponic systems.